Komposisi Karawitan Composition “Samsara” | Komposisi Karawitan “Samsara” - I Made Raka Adnyana Raka; Saptono - (GHURNITA: Jurnal Seni Karawitan, 2022)
Karawitan composition "Samsara" is an innovative Karawitan composition inspired by the process of human life in the world. This life cycle starts from the birth of humans into the world, grows into children, teenagers to adults, and finally leaves the rough body to nirvana. The stylist composed this work in a structured manner to describe how the process of human life occurs. The musical element of this work is the adoption of keroncong techniques which are transferred to the Selonding and Caruk ensambels. arranging melody of the flute with a harmony pattern, divided into three melodies, namely melodies 1, 2, and 3. Regardless of the technique, it is focused on processing the tone, melody, tempo, and dynamics, arranged systematically through different patterns on each instrument. , but are related to each other. The structure of this work does not use the Tri Angga naming system (kawitan, pengawawak, and pengcet), but uses the division, namely: part I, part II, and part III, each has a different description which can be described as: Part I describes a human who is just born, then grows into an innocent and cheerful child; Part II Describes humans who step into their teens; Part III describes humans who step into adulthood and eventually die.